Learning through “Research Cognitive Theory”: A new framework for developing 21st century research skills in secondary school students - Noora J., Al-Thani (2025)
This study introduces a novel framework for High School Research Cognitive Learning Program (HSRCLP), focused on developing 21st century research skills (including research behavior, scientific identity, and values for the scientific community) among high school students. Drawing on a novel framework of “Research Cognitive Theory” (RCT) and empirical evidence, the HSRCLP represents a paradigm shift in secondary education, offering a dynamic research learning environment to enculturate research skills in students. The RCT in the HSRCLP is grounded within Social Learning Theory (SLT) & Social Cognitive Theory (SCT), incorporating the principles of challenge-based learning (CBL) and blended problem & project-based learning (PBL + PjBL) pedagogical approaches. To demonstrate its effectiveness, a two-group pre-post survey method was employed, involving 230 high school students across 10 batches. Statistical analysis revealed significant improvements in research attitudes among high-performing students (experiment group 1) exposed to the HSRCLP compared to the control group. Subsequent intervention for average or low-performing students (experiment group 2) also yielded substantial gains in research attitudes, highlighting the program's effectiveness across academic spectrums. Therefore, the HSRCLP demonstrates promise in bridging the gap between theory and practice, offering secondary education practitioners an evidence-based approach to nurture secondary students' 21st research century skills. Educators and policymakers are encouraged to integrate RCT-based frameworks into curricula and explore its scalability in various educational settings to enhance its impact on developing scientific identity and research-driven behaviors in students.